Inclusion in physical education: Perceptions of Irish and Swiss student teachers following participation in a European exchange programme - Marron, Susan; Morris, Sonia (European Journal of Adapted Physical Activity, 2018)
This study focused on inclusion in physical education (PE) and investigated, using the theory of planned behaviour, how a teacher education exchange programme across two European countries: (i) influenced the attitudes of student teachers (ST) towards inclusion; (ii) critically challenged the subjective norm; and (iii) impacted on the confidence of STs towards inclusive practice in PE lessons. The methodology used was qualitative (n=6) and included focus group interviews and reflective reports. Four themes emerged from a thematic analysis of the data: (i) understandings of inclusion in mainstream PE; (ii) learned methods of including children with special educational needs (SEN) in mainstream PE; (iii) perceived barriers to inclusive practice; and (iv) the important role of professionals in inclusion.  Teaching education universities should be mindful of the expectations and practices with regards to inclusion within their respective countries and provide opportunities for STs to critically question subjective and behavioural norms. A cultural exchange is recommended as a proposed teaching methodology at teacher education based on the findings of this study. The opportunity to compare inclusive practice in two different countries brought the subjective norm into consciousness for participants in this study and facilitated critical questioning of this norm. Findings highlight the benefits to including intercultural opportunities into teacher education specifically for PE teachers.
Keywords: Special educational needs; inclusion; universal design; differentiation; European exchange; theory of planned behaviour